Effect of A-site deficiency on the structural and magnetic properties of La0.8−x□xNa0.2−x□xMnO3 oxides and estimation of the magnetocaloric behavior. (February 2019) - Ameur, N.; Elleuch, F.; Triki, M.; Dhahri, E.; Bessais, L.; Hlil, E.K.
Abstract: The morphological, structural, magnetic and magnetocaloric properties of perovskite manganite oxides La0.8−x □x Na0.2−x □x MnO3 are studied with x = 0 and 0.1. The X-ray diffraction (XRD) data were analyzed by Rietveld refinement technique which reveals that the samples crystallized in a rhombohedral structure with R 3 ¯ c space group. As for the magnetic measurements, it is found that the two samples undergo a transition from the ferromagnetic state (FM) to paramagnetic state (PM) with the increase of temperature. The transition temperature, called the Curie temperature (TC ), decreases from 324 K for the parent compound (x = 0) to the range of room temperature (304 K) for x = 0.1. Moreover, from magnetization measurements versus magnetic applied field, we studied the magnetocaloric effect (MCE) by the determination of the magnetic entropy change ΔSM . The maximum magnetic entropy changes Δ S M Max increases from 2.91 J/kg.K for x = 0–3.23 J/kg.K for x = 0.1 under an applied magnetic field of 2 T. The Relative Cooling Power (RCP) values were found to reach 76.13 J/K and 70.36 J/K for x = 0 and 0.1, respectively, for the same applied magnetic field (μ0 H = 2 T). Thanks to the mentioned values obtained around the Curie temperatures, these materials are suggested to be good candidates as magnetic refrigerants for magnetic refrigeration in the above-room and room temperature range. Besides, a mixture of these two materials may form a composite refrigerant working in a larger temperature range limited by their TC . Highlights: Study of structural and magnetic properties of the samples the general formula La 0.8 - x Na 0.2 - x MnO 3 (x = 0 and 0.1). Ferromagnetic–paramagnetic phase transition. A typical second order magnetic transition near Tc . Study of magnetocaloric effect of La0·8 Na0·2 MnO3 and La0.7 □0.1 Na0.1 □0.1 MnO3 compounds. The studied compounds may be suitable candidates to be used in magnetic refrigeration.